Nondegrading land use strategies for tropical hillsides - Jackson, Lee Ann; Scherr, Sara J. (International Food Policy Research Institute, 1995)
By 2020, current food production methods will be unable to meet the food demands of the growing world population. As high-productivity lands become more scarce and food demand increases, people will increase the cultivation of lands that were once considered too fragile for intensive use. Large populations will depend on hillside agricultural production for their livelihoods. Although sloping lands are sensitive to erosion, nondegrading land uses do exist. These alternative uses support local economic development while protecting watershed stability. To prepare for 2020, policies must evolve that address the needs of hillside inhabitants while promoting land use systems that are appropriate to the physical and economic conditions of these areas. To support the sustainable use of hillsides, policies must be compatible with population distribution, economic incentives, and physical conditions. With supportive policies, direct improvements in production, reduced environmental degradation (downslope and downstream), and improved welfare conditions will provide needed economic and social benefits to these often neglected areas.